From "May Contain" to "Does Contain"? The price and trade effects of introducing strict information requirements under the biosafety protocol article 18.2(a) in the case of maize - Gruère, Guillaume P.; Leroy, Laetitia (International Food Policy Research Institute, 2010)
This note summarizes a study on the effects of implementing strict information requirements under Article 18.2(a) of the Cartagena Protocol on Biosafety, examining the case of maize. The results suggest that such measures would increase maize prices and distort international trade, with significant economic losses in Protocol member countries.